Novel topology of DC circuit breaker and current interruption in HVDC networks. Issue 4 (3rd February 2017) - Guo, Qinglei; Yoon, Minhan; Park, Jungsoo; Jang, Gilsoo
Abstract : With the emerging growth of high‐voltage direct current (HVDC) transmission in modern power systems, the HVDC grid has become a hot topic in recent academic research and real projects. In the DC grid, DC faults can have very serious consequences, and so the faulty DC parts need to be rapidly isolated from the system. Compared to the full‐bridge converters for the DC grid, DC circuit breakers are preferred to deal with this problem economically. In this paper, the self‐excited resonant DC circuit breaker is reviewed. Then, a novel scheme of hybrid DC circuit breaker is introduced, and the operation principle of the proposed circuit breaker is described in detail. Finally, a four‐terminal HVDC grid based on a modular multilevel converter (MMC) is used as the DC test system in PSCAD/EMTDC to verify the validity of the proposed DC circuit breaker. From the simulation results, it is seen that the proposed DC circuit breaker has advantages on current interruption time, voltage on DC circuit breaker, investment, etc. © 2017 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.